Kebijakan Luar Negeri Turki Melawan Partiya Yekitiya Demokrat di Suriah Utara (2016-2019) - Rifqy Alief Abiyya; Rizky Hikmawan (Jurnal ICMES, 2026)
This research explores Turkey's strategic response to Kurdish armed groups, specifically the Partiya Yekitiya Demokrat (PYD) and its military faction, the Yekineyen Parastina Gel (YPG), operating near the Turkish-Syrian border. The Turkish government regards the PYD/YPG as the Syrian branch of the Partiya Karkeren Kurdistan (PKK), a Kurdish separatist group in domestic insurgency. The conflict between Turkey and the Kurds has persisted for decades, with peace initiatives yet to materialize. Turkey is worried about the PYD/YPG's growing power in northern Syria, especially near the border with Turkey, because it could lead to expansion that threatens Turkish sovereignty and national security. In response, Turkey has launched a series of cross-border military operations to counter this expansion, such as Operation Euphrates Shield (2016), Operation Olive Branch (2017), and Operation Peace Spring (2019). This study uses the offensive neorealism theory to explain that Turkey's military actions are not only defensive but also strategic moves to establish regional dominance in the Middle East. This research adopts a qualitative descriptive methodology, aiming to describe and analyze PYD/YPG as a threat to Turkey and the Turkish government's policy response through military operations to protect its sovereignty and national security. Data collection techniques involve document analysis of prior studies and interviews with selected experts. The findings indicate that Turkey's military operations are primarily driven by national security threats, particularly due to PYD/YPG’s collaboration with the PKK and their repeated attacks on Turkish territory. In practice, the policy has succeeded in limiting the PYD/YPG’s territorial expansion, especially in autonomous Kurdish zones in northern Syria. Nevertheless, it has not fully resolved the root causes of the conflict between Turkey and Kurdish forces.